Protocolo multiprofissional de atenção às urgências e emergências para imigrantes nos serviços de saúde - Carvalho, Luciano de Moura (2019)
INTRODUCTION: In the history of mankind, there have always been displacements of people through persecution, conflict, war, poverty, extreme poverty and hunger. The International Organization for Migration (IOM) reported that the number of international migrants reached 259 million in 2017, demonstrating the need for a new policy with government actions that provide guarantees of basic health rights for the immigrant. In Brazil, the Emergency and Emergency Network (RUE) is one of the forms of access to health services, and must be qualified to meet this new demand. In this scenario, the adoption of evidence-based protocols assists in the management of health services and in the standardization of care flows, improving the quality of care provided. OBJECTIVE: The purpose of this study was to elaborate a multiprofessional protocol of health services in emergency and emergency care for the care of immigrants in a municipality of the State of Goiás. METHODOLOGY: The elaboration of the respective protocol was carried out from a study with approach in action research with the participation of 32 health professionals of the RUE of the city of Aparecida de Goiânia-GO, following three phases: (1) the health action for the knowledge and the approximation of the Haitian population, (2) project presentation meeting, information gathering, discussion and protocol construction, and (3) consolidation and training. RESULTS: The development of the protocol defined the following topics as more pertinent: the initial approach and the reception of the immigrant, the attendance with Risk Classification, the attendance sheet with translation into French, Spanish and English as a facilitator for assistance to the immigrant, social service and medical approach, among other aspects. FINAL CONSIDERATIONS: With this, this multiprofessional protocol was an important tool to guide the organization of the services of assistance to immigrants in addressing the emergencies and emergencies of the RUE in Aparecida de Goiânia-GO, and could be used as a model for RUE in other municipalities , especially those located in border regions, and it is also suggested to carry out intervention research concerning the application of this protocol.